INTER REGIONAL GOVERNMENT COOPERATION - Emanuel Sujatmoko (Kumpulan Jurnal Mahasiswa Fakultas Hukum, 2013)
ABSTRACTThe regional administration based on autonomy often can not be done alone, butmust be undertaken in collaboration with other local governments. In the area of intergovernmental cooperation sometimes born disputes relating to the implementation of the agreed cooperation. To settle disputes born of cooperation among local governments are expected to finalize the parties amicably, but if consensus fails, then the settlement is done through the Governor or the Minister of the Interior. The dispute resolution emphasizes aspects of monitoring or politics. For the settlement of disputes which were born as a result of cooperation among local governments need to go through the courts, through the Supreme Court after deliberation and efforts through the Governor or the Minister of the Interior has been taken, but there are parties to a dispute can not accept the verdict.Keywords: Cooperation between local governments, Authority